2020
DOI: 10.1017/s0021932019000889
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use in Eswatini: do contextual influences matter?

Abstract: This study sought to investigate the determinants of current use of modern contraceptives beyond the individual level in Eswatini (formerly Swaziland). Previous studies have overlooked the role of community characteristics such as socioeconomic development, women’s empowerment and fertility norms in shaping contraceptive use. Hierarchical structured subsample data of 4112 sexually experienced women from the 2007 Eswatini Demographic Health Survey were analysed using multilevel logistic regression to identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The findings further show that the community's access to mass media was associated with increased odds of antenatal service utilization (Ononokpono et al, 2013). A study conducted in Eswatini indicated at the bivariate level that women living in communities with lower levels of media exposure had reduced rates of contraceptive use (Odimegwu & Chemhaka, 2021). In Ethiopia, communities with higher electronic media possession had an increased likelihood of family planning use compared to communities with lower reports of electronic media possession (Alemayehu et al, 2020).…”
Section: Community Mass Media and Access To Safe Watermentioning
confidence: 83%
See 3 more Smart Citations
“…The findings further show that the community's access to mass media was associated with increased odds of antenatal service utilization (Ononokpono et al, 2013). A study conducted in Eswatini indicated at the bivariate level that women living in communities with lower levels of media exposure had reduced rates of contraceptive use (Odimegwu & Chemhaka, 2021). In Ethiopia, communities with higher electronic media possession had an increased likelihood of family planning use compared to communities with lower reports of electronic media possession (Alemayehu et al, 2020).…”
Section: Community Mass Media and Access To Safe Watermentioning
confidence: 83%
“…However, after controlling for individual factors, the contextual factors were insignificantly associated with contraceptive use. This shows that contextual factors may have important implications for contraceptive use (Odimegwu & Chemhaka, 2021). The beliefs and myths in communities play a vital role in influencing reproductive health outcomes in different parts of Sub-Saharan Africa.…”
Section: Community Beliefs and Mythsmentioning
confidence: 97%
See 2 more Smart Citations
“…Using the 2017 GMHS, we investigate the factors that account for women’s immediate and subsequent or future use of contraception following abortion, considering socio-demographic, reproductive, partner-related, and facility-level factors. Several studies have investigated factors associated with contraceptive use among women in reproductive ages [ 14 18 ] but, abortion seekers have unique characteristics that put them at risk of experiencing multiple abortions. Abortion seekers in Ghana are younger, reside in urban areas, have a higher socio-economic status, and have no child or few children [ 19 ].…”
Section: Introductionmentioning
confidence: 99%